Design, synthesis, in silico ADMET studies and anticancer activity of some new pyrazoline and benzodioxole derivatives - TOK, FATİH; KAYMAKÇIOĞLU, BEDİA (My University, 2022)
A new series of 2-pyrazoline derivatives starting from substituted benzodioxole chalcones were designed and synthesized. IR and 1H NMR spectral data and elemental analysis were used to characterize the structures of the synthesized compounds. The cytotoxic activities on HeLa, MCF-7 cancer cell lines and NIH-3T3 for these compounds were tested by using MTT assay. Among the synthesized compounds 2d, 2j, 3j and 3n against MCF-7 cells, and 3c against HeLa exhibited significant cytotoxic activity with IC50 between 10.08 and 27.63 mu M. Compound 3f showed the most potent anticancer activity against both cancer cells with good selectivity (IC50 = 11.53 mu M on HeLa with SI = 81.75 and IC50 = 11.37 mu M on MCF-7 with SI = 82.90). Furthermore, in silico ADMET analyses were performed and the drug-likeness properties of the compounds were investigated.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Pyrazoline; carboxamide; anticancer activity; breast cancer; cervical cancer